2022
DOI: 10.1080/00207454.2022.2126774
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine β-hydroxylase polymorphism rs1611115 and serum levels with psychiatric disorders in Pakistani population

Abstract: Dopamine β-hydroxylase (DBH) is a copper-containing enzyme that has an important role in maintaining the cellular homeostasis between the two neurotransmitters, dopamine (DA) and nor-adrenaline (NA). DBH functional polymorphisms are associated with multiple neuro-psychiatric conditions and are found to alter the DBH protein levels in serum, affecting DBH enzymatic activity. The current study was conducted to determine the genetic association of DBH functional polymorphism rs1611115 and its effect on DBH levels… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…We compared allele frequencies of the studied control cohort to the PJL dataset from the 1000 Genomes project and found significant differences for three of the variants i.e., rs2896218, rs3779550 and rs2024233. Hashmi et al, (2022) 44 and Khan et al, (2020) 42 from our research group reported similar observations, one reason for this could be that the majority of the samples collected for this and the previous studies were from the twin cities of Rawalpindi and Islamabad. Both these cities comprise people from diverse backgrounds including a high influx of Pashtuns from Khyber Pakhtunkhwa.…”
Section: Discussionsupporting
confidence: 81%
“…We compared allele frequencies of the studied control cohort to the PJL dataset from the 1000 Genomes project and found significant differences for three of the variants i.e., rs2896218, rs3779550 and rs2024233. Hashmi et al, (2022) 44 and Khan et al, (2020) 42 from our research group reported similar observations, one reason for this could be that the majority of the samples collected for this and the previous studies were from the twin cities of Rawalpindi and Islamabad. Both these cities comprise people from diverse backgrounds including a high influx of Pashtuns from Khyber Pakhtunkhwa.…”
Section: Discussionsupporting
confidence: 81%